Edukasi Pencegahan Anemia pada Remaja Putri - Nel Efni; Tina Yuli Fatmawati (3031-8572, 2022)
Prevalence of anemia in Indonesia in women aged 15-24 years is 84.6%. Based on the Jambi City Service Health Profile, the prevalence in 2017 was that the number of teenage girl suffering from anemia was 262 (4.5%) of the total number of 5841 young women. The Teenage are more susceptible to anemia than adolescent boys. This is because the need for iron in women who are already menstruating is three times greater than that of boys. The purpose of this service is to increase knowledge about anemia in adolescents at SMP N 19 Jambi City. The service method applied is education (lectures, questions and answers, discussions). The media used are leaflets and banners. This service was held in January 2022 for teenage girls at SMP N 19 Jambi City with a total of 25 students. The results of the service were obtained after education. Most of the students (100%) understood the definition, causes, symptoms, management and prevention of anemia.